Case Report: Colon malignant tumor caused by retroperitoneal small round cell undifferentiated sarcoma - Wei, Yuqin; Zhang, Zhiyong; Long, Chenyan; Huang, Xiaoliang; Tang, Weizhong; Mo, Xianwei; Liu, Jungang (Frontiers in Oncology, 2023)
Small round cell undifferentiated sarcoma is a rare and highly invasive group of malignant bone and soft tissue tumors, often associated with a high misdiagnosis rate. The patient in this case was a 34year-old male who presented with a two-month history of abdominal pain that worsened over the past two weeks. Elevated levels of tumor markers CA19-9 and CA72-4 were observed. Imaging revealed a substantial, well-vascularized mass in the lower left abdomen, located in the posterior abdominal cavity, invading the descending colon and the root of the small mesentery, and infiltrating the serous layer. The lesion was extensively resected without any postoperative complications. Microscopic examination indicated a combination of mucinous adenocarcinoma (approximately 30%) and small round cell undifferentiated sarcoma (approximately 70%). The patient was followed up for six months, and one month after surgery, a recurrence of the tumor was observed in the left paracolonic sulcus area, with metastases to the abdominal wall, peritoneum, and medial iliac muscles. Chemotherapy and targeted therapy were administered, and the patient currently survives with the presence of tumors. Small round cell undifferentiated sarcoma is an uncommon and highly invasive tumor, and clinical surgeons need to raise their awareness and realize to the maximum extent possible that this disease can be described through a multi-modal combination of immunohistochemistry and genetic test to improve diagnostic accuracy and reduce missed diagnoses. Further research in the field of biology is necessary to explore targeted drugs specifically suitable for this disease.